Chemical Imaging of Mixed Metal Oxide Catalysts for Propylene Oxidation: From Model Binary Systems to Complex Multicomponent Systems. Issue 10 (30th March 2021) - Sprenger, Paul; Stehle, Matthias; Gaur, Abhijeet; Weiß, Jana; Brueckner, Dennis; Zhang, Yi; Garrevoet, Jan; Suuronen, Jussi‐Petteri; Thomann, Michael; Fischer, Achim; Grunwaldt, Jan‐Dierk; Sheppard, Thomas L.
Abstract: Industrially‐applied mixed metal oxide catalysts often possess an ensemble of structural components with complementary functions. Characterisation of these hierarchical systems is challenging, particularly moving from binary to quaternary systems. Here a quaternary Bi−Mo−Co−Fe oxide catalyst showing significantly greater activity than binary Bi−Mo oxides for selective propylene oxidation to acrolein was studied with chemical imaging techniques from the microscale to nanoscale. Conventional techniques like XRD and Raman spectroscopy could only distinguish a small number of components. Spatially‐resolved characterisation provided a clearer picture of metal oxide phase composition, starting from elemental distribution by SEM‐EDX and spatially‐resolved mapping of metal oxide components by 2D Raman spectroscopy. This was extended to 3D using multiscale hard X‐ray tomography with fluorescence, phase, and diffraction contrast. The identification and co‐localisation of phases in 2D and 3D can assist in rationalising catalytic performance during propylene oxidation, based on studies of model, binary, or ternary catalyst systems in literature. This approach is generally applicable and attractive for characterisation of complex mixed metal oxide systems. Abstract : See the bigger picture : Mixed metal oxide catalysts often have a highly complex structure. Spatially‐resolved characterisation tools applied in 2D and 3D can help to define the presence and interaction of different metal oxide phases within a catalyst particle. In turn this can reveal important information on the structure and function of mixed metal oxide catalysts.